The miR-143/miR-145 cluster and the tumor microenvironment: unexpected roles - Almeida, Maria Inês (Genome Med, 2016)
miR-143 and miR-145 have been widely described as tumor suppressors. Recent findings suggest these microRNAs (miRNAs) have a critical role that affects the stroma rather than epithelial cells. Understanding the part played by the miR-143/miR-145 cluster in the tumor microenvironment is essential for the development of future miRNA-related therapies.